Exploiting Synergy: Immune-Based Combinations in the Treatment of Prostate Cancer - Burotto, Mauricio; Singh, Nishith; Heery, Christopher R.; Gulley, James L.; Madan, Ravi A. (Frontiers in Oncology, 2014)
Cancer treatment is being revolutionized by the emergence of immunotherapies such as immune check point inhibitors and therapeutic cancer vaccines. Prostate cancer has is amenable to such therapeutic approaches. The improved understanding of the relationship between the immune system and tumors has allowed therapeutic targeting of immune checkpoints and tumor associated antigens to be developed. Furthermore, interventions used in prostate cancer are capable of impacting the immune system. As demonstrated by preclinical data and emerging clinical data, radiation therapy, anti-androgen therapy and chemotherapy can be used with immunotherapies to obtain synergistic results. Current and future clinical trials will further investigate these principals as immunotherapeutics are combined with each other and standard therapies for optimal clinical utility.